The turntable tribe: a communications campaign to raise awareness about the effects of excessive fast furniture consumption and encourage environmentally sustainable shopping habits among homeowners - Tan, Gerald Zheng Jie (Nanyang Technological University, 2023)
The Turntable Tribe is a communications campaign that aims to raise awareness about the effects of excessive fast furniture consumption and encourage environmentally sustainable shopping habits among homeowners. As the least-recycled household item, furniture is the second largest contributor to urban waste, with 12 million tons of furniture being thrown out each year in the US alone.